1973
DOI: 10.1159/000197315
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Endogenous Gastrin Release to Affect Serum Insulin

Abstract: The effect of endogenously stimulated gastrin on serum insulin level was investigated in 7 normal subjects. Glycine by mouth was chosen as gastrin releaser. The glycine drink caused a significant rise of serum gastrin and insulin levels either in the fasting state or during glucose stimulation. However, serum insulin response of same magnitude occurred when stimulation of gastrin secretion was prevented to occur by infusing glycine into the duodenum. The results suggest that post-glycine rise in serum insulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1974
1974
1976
1976

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Basal gastric acid output (BAO) was measured on four 15-min aspirates collected before histamine stimulation. Maximal gastric acid output (MAO) was determined as previously described [5], Serum gastrin measurements were performed in triplicate by radioimmunoassay as previously reported (1). Antiserum was supplied by Wilson Laboratories, Chicago, III.…”
Section: Methodsmentioning
confidence: 99%
“…Basal gastric acid output (BAO) was measured on four 15-min aspirates collected before histamine stimulation. Maximal gastric acid output (MAO) was determined as previously described [5], Serum gastrin measurements were performed in triplicate by radioimmunoassay as previously reported (1). Antiserum was supplied by Wilson Laboratories, Chicago, III.…”
Section: Methodsmentioning
confidence: 99%
“…These results suggest that physiological concentrations of gastrin contribute little to the insulin response. Budillon et al [9], who studied gastrin and insulin release following oral and intraduodenal stimuli, reached similar conclusions. Rehfeld and Stadil [10] have shown that intravenous administration of gastrin will only stimulate insulin release when administered in doses which result in serum gastrin concentrations above the physiological range.…”
Section: Discussionmentioning
confidence: 66%
“…5) Gastrin secretion in duodenal ulcer patients is also abnormally increased, at least during meals (35,36). Serum levels in these patients and those of food-stimulated normal subjects (37) are, however, placed so much to the left on the dose-response curve (4) that it is difficult to demarcate insulinogenic effects of endogenous gastrins in these conditions. 6) Patients with severe kidney damage are hypergastrinemic, but their general metabolic derangement, including abnormal levels of betacytotrophic hormones other than gastrin, makes them unfit for studies like the present.…”
Section: Discussionmentioning
confidence: 99%